Study on Characteristics of Sediment and Sedimentation Rate at Sungai Lembing, Kuantan, Pahang - Nadiatul Adilah, Ahmad Abdul Ghani; Norasman, Othman; Mohd Khairun Hafiz, Baharudin (Elsevier Ltd, 2013)
River is important in human life. River is very useful and has various functions in human life such as for domestics, economics, connection for one place to others place and many more. The main function of the river is to flow the water to the water storage or sea. River also brings the sediment from upstream or from erosion process. Sediments may affect the characteristics and the rate of the river. The study of sedimentation rate is quite important for development our country. It also can avoid the problem which related to our human society such as flood and water quality. As example, the depth of river become shallow if the sedimentation occurred. It also will make the quantity of aquatic life will reduced. This study was carried out to determine the sedimentation rate for five locations in the study area at Sungai Lembing, Kuantan, using Duboys and Schoklitsch equation. The highest sedimentation rate using Duboys is 2.06 lb-sec/ft was obtained at Station 3 and the lowest sedimentation rate is 0.073 lb-sec/ft also at Station 3 but in different day. Meanwhile, by using Schoklitsch equation, the highest rate is 1.12 lb-sec/ft at Station 1 and the lowest rate at Station 5 with 0.263 lb-sec/ft. The results for Duboys indicated that the rate is related to the mean size of sediment and the cross section of the river. By using Schoklitsch, the results depend on the flow rate of the river. If the flow rate higher, the sediment rate will also increase. The sediment sample sieving test results was classified using U. S. Army Corps of Engineer (USACE). The major size at Sungai Lembing for every station is in range between 2 mm-0.5 mm (Medium sand) and the minor size of sediment for the five ungauged station is 0.25 mm- 0.0625 mm (very fine sand).